Impact of growth retardants on corn leaf morphology and gas exchange traits - Kasele, I.; Shanahan, J.F.; Nielsen, D. (1995)
Growth retardant (GR) application often produces compact plants with dark green foliage and reduced leaf size. These morphological alterations can affect leaf gas exchange and biochemical traits associated with photosynthesis. We conducted greenhouse experiments by growing corn (Zea mays L.) plants under optimum water and nutrient conditions to evaluate the impact of two GR treatments, a seed applied treatment of BAS110.. W (1-(2,4-dichlorophenyl)-2-methoxy-1-methyl-2-(1H-1,2,4-triazol-1-yl) ethanol) at 250 mg kg-1 of seed and an ethephon (2-choloroethyl phosphonic acid) treatment (a foliar-applied solution containing 100mg a.i ethephon characteristics (leaf stomatal conductance to H20 vapor (gs), leaf intercellular CO2 concentration (C1) and leaf CO2 exchange rate (CER) and water use efficiency, and other plant morphological traits. A CERvs. C1 response curve was also determined to assess the carboxylation efficiency for control and treated plants. Both GR reduced total plant leaf area and dry weight by about 21 to 31% relative to the control but increased specific leaf weight and weighted stomatal density by 7 to 19%. Leaf protein and chlorophyll contents were nearly doubled in GR- treated plants.